Routledge Handbook of Global Environmental Politics Second Edition 2022 - Harris, Paul G. (Taylor & Francis, 2022)
This handbook brings together leading international academic experts to provide a comprehensive and authoritative survey of Global Environmental Politics. Fully revised, updated and expanded to 45 chapters, the book: • Describes the history of global environmental politics as a discipline and explains the various theories and perspectives used by scholars and students to understand it. • Examines the key actors and institutions in global environmental politics, explaining the roles of states, international organizations, regimes, international law, foreign policy institutions, domestic politics, corporations and transnational actors. • Addresses the ideas and themes shaping the practice and study of global environmental politics, including sustainability, consumption, expertise, uncertainty, security, diplomacy, North-South relations, globalization, justice, ethics, public participation and citizenship. • Assesses the key issues and policies within global environmental politics, including energy, climate change, ozone depletion, air pollution, acid rain, transport, persistent organic pollutants, hazardous wastes, rivers, wetlands, oceans, fisheries, marine mammals, biodiversity, migratory species, natural heritage, forests, desertification, food and agriculture. This second edition includes new chapters on plastics, climate change, energy, earth system governance and the Anthropocene. It is an invaluable resource for students, scholars, researchers and practitioners of environmental politics, environmental studies, environmental science, geography, globalization, international relations and political science.